PENGARUH PEMBIASAAN LITERASI Al-QUR’AN SECARA DARING TERHADAP KOMPETENSI MENGANALISI ISI KANDUNGAN QS AN-NISA AYAT 59 DI KELAS XI IPS SMA NEGERI 2 SUMEDANG - moch hilman taabudilah; Dedeh Sumiati (STAI Sebelas April Sumedang, 2020)
Al-Qur'an literacy plays a very important role in fostering a reading culture by increasing faith and piety as well as noble morals through education in schools. Al-Qur'an literacy is part of the School Literacy Movement (GSL) program, as an effort to improve reading culture and develop character. Familiarization with Al-Qur'an literacy hopes to increase competence in analyzing the contents of Qs. An-Nisa verse 59. The results of this research show that; (1) familiarization with Al-Qur'an literacy online in class An-Nisa verse 59 at SMA Negeri 2 Sumedang with a percentage of 62% is in the quite good category, and (3) the influence of online literacy of the Al-Qur'an on competence in analyzing the contents of Qs. An-Nisa verse 59 in class XI-7 SMA Negeri 2 Sumedang has a unidirectional relationship (b=0.610), a strong level of closeness. (r=0.882) and the Al-Qur'an literacy habituation variable contributes to the competency variable analyzing the contents of Qs. An-Nisa verse 59 is 67.6% with fairly good criteria, then based on the results of hypothesis testing (t-test), it shows that the hypothesis (Ha) is accepted, meaning that the influence variable of Al-Qur'an literacy habituation has an effect on the competency variable of analyzing content Qs content. An-Nisa verse 59